Differential detection of strong acids in weak acids: a combination of a benzimidazole-carbazole backbone with AIE luminophores as highly sensitive and selective turn-on fluorescent probes - Lin, Pei-Chi; Lin, Yu-Ting; Liu, Kuan-Ting; Chen, Meng-Sin; Zhang, Yong-Yun; Li, Jie-Cheng; Leung, Man-kit (New journal of chemistry, 2022)
o -BzcDPE and p -BzcDPE have been synthesized and used as probes for strong acid detection. The probes contain aggregation-induced emission luminogens (AIEgens) that are incorporated with a benzimidazole-carbazole backbone. Both probes show turn-on green fluorescence with a good contrast in the presence of trace amounts of strong acids in a weak acid environment. These probes are not only suitable for visual detection of strong acids, but also exhibit high selectivity, excellent sensitivity, and short response time and are capable of quantitative detection of strong acids with a good linear relationship. A concentration of H 2 SO 4 as low as 1 mol% in acetic acid can be differentiated. The fluorescence-turn-on mechanisms are due to protonation on the benzimidazole moiety that have been proved by X-ray crystallographic analysis and NMR spectroscopy. With the combination of a benzimidazole-carbazole backbone and AIE luminophores, highly sensitive and selective turn-on fluorescent probes are achieved and applicable for differential detection of strong acids in weak acids.